Hubungan Antara Body Dissatisfaction Ibu dan Body Dissatisfaction Anak Perempuan - Evahani, Luki (University of Surabaya, 2012)
Body dissatisfaction can be predicted that the mother had an impact on their children because the mother is not happy with her body will communicate such dissatisfaction with her children, so it can make children become dissatisfied with her body (Ogden, 2007). But this mother´s body dissatisfaction can affect the child´s body dissatisfaction if the mother and child have a good relationship. Mother and child relationship can be measured based on the closeness between mother and child, mutual communication, appreciation, togetherness, understanding and support from the mother, and the mother trust to her child´s. Measurement of maternal and child relationship using the aspect of Konopka (in Shofiana, 2005). Body dissatisfaction of mothers and children can be measured using a questionnaire Body Shape Questionnaire (BSQ), which measures the level of attention to the feelings of obese subjects.This study aims to determine the relationship between mother body dissatisfaction and daughter body dissatisfaction with a controlling relationship between mother and child. Respondents of this research are two of 60 female students of Faculty of Psychology, University of Surabaya aged 18-21 years who have a body mass index (BMI) in the normal category and 60 mothers of subjects aged 40-60 years.Based on the results of the study, body mass index (BMI) mothers are mostly located on level one of obesity. Also the women subjects (55%) and children (68.3%) had medium levels of body dissatisfaction. The test results by using partial correlationtechniques stating there is a significant relationship between mother body dissatisfaction and child´s body dissatisfaction with a controlling mother and child relationship (r = .3864, sig =.003 <.05). This suggests that mother´s body dissatisfaction was significantly correlated with the child´s body dissatisfaction without significant influence from the quality of mother andchild´s relationship.